2007
DOI: 10.1152/ajpregu.00048.2007
|View full text |Cite
|
Sign up to set email alerts
|

Centrally administered vasopressin cross-sensitizes rats to amphetamine and drinking hypertonic NaCl

Abstract: Prior sodium restriction cross-sensitizes rats to the psychomotor effects of amphetamines and vice versa. Repeated central injections of vasopressin (VP) induce a psychomotor sensitization similar to amphetamine sensitization and repeated sodium deficiency. Thus brain VP signaling may be a common mechanism involved in mediating these two motivational systems. In experiment 1, we tested the hypothesis that rats previously sensitized to central VP would show enhanced psychomotor responses to amphetamine. Rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Subcutaneous pretreatment with AVP completely antagonised the increase in locomotor activity induced by acute cocaine or AMPH injection . On the other hand, microinjections of AVP in the lateral ventricles produced an increase in locomotor activity, and animals treated with AVP had a higher psychomotor response to AMPH, indicating cross‐sensitisation between AVP and AMPH . Regarding METH, in a conditioned place preference model with a priming injection reinstatement phase, systemic treatment with a V1b antagonist during the extinction phase diminished METH‐seeking reinstatement behaviour .…”
Section: Psychostimulants and Vasopressinmentioning
confidence: 99%
“…Subcutaneous pretreatment with AVP completely antagonised the increase in locomotor activity induced by acute cocaine or AMPH injection . On the other hand, microinjections of AVP in the lateral ventricles produced an increase in locomotor activity, and animals treated with AVP had a higher psychomotor response to AMPH, indicating cross‐sensitisation between AVP and AMPH . Regarding METH, in a conditioned place preference model with a priming injection reinstatement phase, systemic treatment with a V1b antagonist during the extinction phase diminished METH‐seeking reinstatement behaviour .…”
Section: Psychostimulants and Vasopressinmentioning
confidence: 99%
“…Interestingly, administration of SR49059 (AVPV 1A Rs antagonist) in zebrafish led to a decrease in the MDMA-induced anxiolytic effect [ 98 ], which further supports the hypothesis of the bidirectional effects of AVPV 1A Rs and AVPV 1B Rs antagonists. In terms of AVP effects on animals’ locomotion, it has been shown that AVP treatment leads to cross-sensitization to amphetamine-induced hyperlocomotion [ 100 ] and that SSR149415 is able to decrease the expression of nicotine-induced locomotor sensitization [ 101 ]. The impact of AVP and AVPRs ligands on depressive-like behavior and memory performance is yet to be discovered.…”
Section: The Impact Of Ot/avp and Otrs/avprs Ligands On Behavioral An...mentioning
confidence: 99%
“…We do not know if such protocol would cross-sensitize with the effects of sodium depletion. Second, the drugs of abuse which cross-sensitize their effects with that of sodium depletion have the potential to influence both energetic and water metabolism as well as interact with hormones that produce neuroplasticity (Acerbo & Johnson, 2011;Grell, Christensen, & Fjalland, 1985;Han, Kelly, Fellingham, & Conlee, 1996;Marchand, 1970;McBride & Flynn, 2007;Mello & Mendelson, 1997;Nencini, Valeri, & Morrone, 1990). Thus, another possible level of difference in the rules of crosssensitization, not mutually exclusive to that dependent on sensory afference to the brain, could reside in physiological or metabolic, and hormonal alterations.…”
Section: Groupmentioning
confidence: 99%